Feedback of Research Findings for Vaccine Trials: Experiences from Two Malaria Vaccine Trials Involving Healthy Children on the Kenyan Coast - Gikonyo, C; Kamuya, D; Mbete, B; Njuguna, P; Olotu, A; Bejon, P; Marsh, V; Molyneux, S (2013)
Internationally, calls for feedback of findings to be made an 'ethical imperative' or mandatory have been met with both strong support and opposition. Challenges include differences in issues by type of study and context, disentangling between aggregate and individual study results, and inadequate empirical evidence on which to draw. In this paper we present data from observations and interviews with key stakeholders involved in feeding back aggregate study findings for two Phase II malaria vaccine trials among children under the age of 5 years old on the Kenyan Coast. In our setting, feeding back of aggregate findings was an appreciated set of activities. The inclusion of individual results was important from the point of view of both participants and researchers, to reassure participants of trial safety, and to ensure that positive results were not over-interpreted and that individual level issues around blinding and control were clarified. Feedback sessions also offered an opportunity to re-evaluate and re-negotiate trial relationships and benefits, with potentially important implications for perceptions of and involvement in follow-up work for the trials and in future research. We found that feedback of findings is a complex but key step in a continuing set of social interactions between community members and research staff (particularly field staff who work at the interface with communities), and among community members themselves; a step which needs careful planning from the outset. We agree with others that individual and aggregate results need to be considered separately, and that for individual results, both the nature and value of the information, and the context, including social relationships, need to be taken into account. Copyright © 2013 Blackwell Publishing Ltd.